A Problem of Information System Integration At a University in Indonesia - Ulya, Dzakiya Ishmatul; Khair, Ashabu; Amrozi, Yusuf (SAINTEKBU, 2022)
Almost all higher education information systems in Indonesia have experienced a problem. The challenge of university data management systems is how to integrate data subsystems in the university's internal environment. This can hinder the process of continuing the university's services. Higher education information systems usually include academic, financial, teaching staff, and graduate information systems. Not all universities have integrated the information system sub-sub. As a result, data duplication and data are out of sync. Data is essential in universities because every year, universities have to manage the data of thousands of students. For this reason, an integrated higher education information system is needed. The research method used in this article is a qualitative descriptive method by describing the facts that occurred. The author uses data collection techniques to study literature by looking for relevant and reliable references. After the authorities were collected, the writer analyzed the data qualitatively. At the end of this article, the author provides a solution to integrate higher education information systems.